PEMANFAATAN INFORMASI CUACA PADA NELAYAN DI WILAYAH KOTA DUMAI - Yasir Prayuna; Indah Desinigraha (Pelantar Press, 2023)
Fishery Conditions in Dumai City, almost all of its production comes from marine fisheries and the rest is aquaculture and others. This great potential makes the fishery sector an important sector that must receive more attention from the government, especially the local government of Dumai City. In recent years, weather and climate conditions that are very diverse are the main challenges in management in various sectors, including the marine and fishery sector. Therefore, this study aims to see how the existing conditions of the Dumai City area and the use of weather information for fishermen in the Dumai City area, including the efforts that can be made by the parties or related agencies. From the existing condition of Dumai City, the education aspect is low but the health aspect is high and the income aspect is middle to lower. Then there is an increasing in understanding and using of weather information for communities that are directly related to the maritime world, especially fishermen by socialization or an activity called the Fisherman Weather Field School.